Analisis Pengaruh Net Interest Margin terhadap Pertumbuhan Laba pada Industri Perbankan: Bukti Empiris dari PT Bank Victoria International Tbk - Santi Sartika; Nisa Nurparidah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Banking performance is greatly influenced by a bank's ability to manage interest income and maintain profit stability, especially in volatile economic conditions. Changes in the Net Interest Margin (NIM) are an important indicator that can affect profit growth, so they need to be examined empirically. This study aims to analyse NIM developments, profit growth developments, and test the effect of NIM on profit growth at PT Bank Victoria International Tbk. This study uses a quantitative approach with an explanatory method. The research population consists of all annual financial reports of PT Bank Victoria International Tbk, and the sample was selected using the purposive sampling technique, namely financial reports for the 2018–2023 period that met the data availability criteria. Secondary data was obtained through official company publications. The analysis was conducted through descriptive analysis, correlation, simple regression, and influence testing using statistical software. The results show that NIM and profit growth fluctuated during the observation period. NIM is positively related to profit growth, but it is not the main determinant of the company's profit increase. Profit growth is more influenced by other factors such as operational efficiency, asset quality, provision expenses, and non-interest income. The implications of this study emphasise the need for a more comprehensive income and risk management strategy, including strengthening the quality of productive assets, diversifying income, and improving cost efficiency, in order to achieve sustainable profit growth.